2-Aminobenzimidazole Organocatalyzed Asymmetric Amination of Cyclic 1,3-Dicarbonyl Compounds - Trillo, Paz; Gómez-Martínez, Melania; Alonso, Diego A.; Baeza, Alejandro (Synlett, 2015)
The use of a trans-cyclohexanediamine benzimidazole derivative as a hydrogen-bond catalyst for the electrophilic amination of cyclic 1,3-dicarbonyl compounds is herein presented. High yields and enantioselectivities varying from moderate to excellent are generally obtained using mild reaction conditions and as low as 1 mol% of catalyst loading.
Keywords: organocatalysis; electrophilic amination; asymmetric catalysis; dicarbonyl compounds; benzimidazole